2015
DOI: 10.1016/s1001-6058(15)60515-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oil-water flow via the correlation of turbine flow meter, gamma ray densitometry and drift-flux model

Abstract: Abstract:The flow rate of the oil-water horizontal flow is measured by the combination of the turbine flow meter and the singlebeam gamma ray densitometry. The emphasis is placed on the effects of the pipe diameter, the oil viscosity and the slip velocity on the measurement accuracy. It is shown that the mixture flow rate measured by the turbine flow meter can meet the application requirement in the water continuous pattern ( o -w flow pattern). In addition, by introducing the developed drift-flux model into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Baotong et al (2019) reported that three of existing empirical correlations such as Xu et al (2008), Li and Xu (2015), and Baotong et al (2019) systematically underestimated the oil fraction data of Rodriguez and Baldani (2012) of the order of -0.234, -0.197, and -0.199 (mean absolute error), respectively. Baotong et al (2019) also reported that three of existing empirical correlations such as Xu et al (2008), Li and Xu (2015), and Baotong et al (2019) systematically underestimated the oil fraction data of Onuoha et al (2016) of the order of -0.0934, -0.120, and -0.146 (mean absolute error), respectively. It has not been identified that the deviation between the calculated and measured oil fraction for both datasets is due to the measurement uncertainty or due to the incomplete modeling of the phenomena.…”
Section: Analytical Model To Predict Oil Fractionmentioning
confidence: 99%
“…Baotong et al (2019) reported that three of existing empirical correlations such as Xu et al (2008), Li and Xu (2015), and Baotong et al (2019) systematically underestimated the oil fraction data of Rodriguez and Baldani (2012) of the order of -0.234, -0.197, and -0.199 (mean absolute error), respectively. Baotong et al (2019) also reported that three of existing empirical correlations such as Xu et al (2008), Li and Xu (2015), and Baotong et al (2019) systematically underestimated the oil fraction data of Onuoha et al (2016) of the order of -0.0934, -0.120, and -0.146 (mean absolute error), respectively. It has not been identified that the deviation between the calculated and measured oil fraction for both datasets is due to the measurement uncertainty or due to the incomplete modeling of the phenomena.…”
Section: Analytical Model To Predict Oil Fractionmentioning
confidence: 99%
“…Accurate flow rate measurement is the important precondition of many industry fields, such as medical, energy, petrochemical engineering, etc(1). Turbine flowmeter has become an important part of flow measurement instruments with high accuracy, good reproducibility and stability (2,3). In addition, turbine flowmeter also can be used as a standard instrument to calibrate other flow measurement instruments.…”
Section: Introductionmentioning
confidence: 99%